Clients' satisfaction with preventive services for malaria during pregnancy in Anambra state, Nigeria - Emmanuel Chijioke Obagha; IkeOluwakpo Ajayi; Gobir A. Abdullahi; Chukwuma David Umeokonkwo (BMC, 2020)
Abstract Background Burden of Malaria in pregnancy (MIP) is still high despite availability of proven cost-effective interventions. Considerable progress has been made on improving antenatal attendance, but MIP preventive services utilization remains low. Factors responsible for this include dissatisfaction with the services provided. We assessed clients' satisfaction with preventative services for malaria during pregnancy delivered at antenatal clinics (ANC) in Anambra State Nigeria. Method We conducted a cross-sectional study among 284 pregnant women attending ANC using multistage sampling technique. Pre-tested semi-structured interviewer-administered questionnaire was used to collect information on socio-demographics, knowledge of malaria in pregnancy services and satisfaction with services. Responses to questions on satisfaction was on a 5-point Likert scale. A cut off of ≥75% of composite score was used to classify respondents as satisfied. For knowledge, every correct answer was scored 1 and incorrect 0; ≥75% of the composite score was graded as good knowledge. Chi square and logistic regression were used to test for association between client satisfaction and independent variables. Results The mean age of participants is 28 years±4.4 years. Overall, 62.2% were satisfied with quality of preventive services for malaria during pregnancy. However, 64.8 and 57.8% were dissatisfied with cost of healthcare and interpersonal relationship with the health workers (HWs). Majority of the respondents (88.73%) had poor knowledge of malaria preventive services during pregnancy. Type of facility (Adjusted odds ratio [aOR] = 2.11; 95%CI: 1.20-3.71) and knowledge (aOR: 0.41; 95%CI: 0.18-0.90) were independently associated with satisfaction with interpersonal relationship. Type of facility (aOR: 0.47; 95%CI: 0.27-0.80) and employment status (aOR: 3.07; 95%CI: 1.39-6.74) were also independently associated with satisfaction with cost of healthcare. Conclusion A fair proportion of respondents were satisfied with the preventive services for malaria during pregnancy provided even though most were dissatisfied with the cost of assessing care and interpersonal relationship with health workers. Uninterrupted availability of long lasting insecticide treated bed nets and intermittent preventive treatment for malaria at all health facilities, subsidized cost of malaria-related commodities, and incentives for good customer satisfaction ratings may remediate the described barriers to seeking preventative care for malaria during pregnancy.